(untitled) (Research, Society and Development, 2022)
Objective: to identify, in the literature, alternative therapies that have already been used to provide emotional support in the face of depression, which can be applied by the nursing team during crisis contexts, such as the COVID-19 pandemic. Methodology: the Integrative Literature Review study used the Medical Literature Analysis and Retrieval System Online (MEDLINE) platform through PubMed, using the MeSH descriptors: complementary therapies AND depression. Results: Of the 8923 titles retrieved by the search, only 15 were included in this review, as they met the selection criteria. The alternative therapies found were divided into 8 categories: Acupuncture, Art Therapy, Ayahuasca, Biodanza, Pranic Healing, Music Therapy, Anise Oil and Yoga. Within this classification, it was possible to observe that the most present therapy in the studies found were Yoga and Acupuncture, all categories of therapies were reported as capable of promoting the improvement of depressive symptoms. Conclusion: the alternative/complementary therapies already used to improve depressive symptoms and/or depression, found in this study, open a range of care that can serve as emotional support for the nursing team in a crisis context such as the one caused by the COVID pandemic. -19. Yoga and acupuncture were described more frequently, being the therapies in which the results and application varieties can be options for the development of group or individual activities, being an option of choice for the nursing team.